Room-temperature 2D semiconductor activated vertical-cavity surface-emitting lasers - Shang, Jingzhi (2018)
Two-dimensional (2D) semiconductors are opening a new platform for revitalizing widely spread optoelectronic applications. The realisation of room-temperature vertical 2D lasing from monolayer semiconductors is fundamentally interesting and highly desired for appealing on-chip laser applications such as optical interconnects and supercomputing. Here, we present room-temperature low-threshold lasing from 2D semiconductor activated vertical-cavity surface-emitting lasers (VCSELs) under continuous-wave pumping. 2D lasing is achieved from a 2D semiconductor. Structurally, dielectric oxides were used to construct the half-wavelength-thick cavity and distributed Bragg reflectors, in favour of single-mode operation and ultralow optical loss; in the cavity centre, the direct-bandgap monolayer WS2 was embedded as the gain medium, compatible with the planar VCSEL configuration and the monolithic integration technology. This work demonstrates 2D semiconductor activated VCSELs with desirable emission characteristics, which represents a major step towards practical optoelectronic applications of 2D semiconductor lasers.